(untitled) (Journal of Asian Development Studies, 2025)
The main objective of this research is to identify the role that affective rumination plays in work family conflict. Moreover, does workload solely cause work-family conflict? Will neuroticism moderate the relationship between affective rumination and work-family conflict? The study found that workload is not the sole factor contributing to work-family conflict; other behavioural and emotional constructs may also be involved. Affective rumination acts as a partial mediator in the relationship between workload and work-family conflict. Neurotic personalities are more vulnerable to affective rumination, leading to increased work-family conflicts. The data collection process consisted of two paper-and-pencil surveys, with a three-week time lag between the two rounds. Convenience sampling has been conducted, and the sample consists of private organisations in Lahore and Karachi. The results indicated that a high neurotic personality trait will increase the chances of work-family conflict. Neurotic personalities are vulnerable to affective rumination; the greater the rumination, the more anxiety will be felt by neurotic personalities, which in result enhances the chance of generating increased work-family conflicts. The findings suggest that workload affects work-family conflict, with affective rumination playing a mediating role, especially among individuals with high levels of Neuroticism. This study will help policymakers and academic researchers understand the impact of workload and neurotic personality on work-family conflict which will bring the design of more balanced policies or work life balance. This study will contribute to the literature by providing insight into the cognitive process of building stress in an employee.